A safety evaluation method and system for a high core wall dam based on construction data - Zicheng Wang; Yingchi Mao; Yaosheng Tan; Qiaoling Shen; Houlei Xu (Journal of Intelligent Construction)
In view of the complex operational conditions and dynamically changing safety risks associated with high core wall dams in the construction period, a comprehensive safety evaluation system for high core wall dams, which utilizes fuzzy theory and emergency response methods, has been developed. Considering the material zoning, load characteristics, and layout of the safety monitoring system specific to high core wall dams and considering the impacts of flood control capacity, foundation conditions, structural safety, operational status, and slope conditions, a safety evaluation method for high core wall dams on the basis of construction data has been proposed. The model dynamically determines the weights of evaluation factors via evaluation criteria and the term frequency–inverse document frequency (TF–IDF) method. It constructs a comprehensive evaluation subordination feature vector, calculates the degree of match between the current safety evaluation result and historical safety evaluation results, and identifies the matching operational conditions. Finally, on the basis of the risk analysis matrix, the risk level of each tier of evaluation factors is determined, and emergency response measures are formulated. This system provides an online monitoring platform for the operational safety of high core wall dams. This approach enhances the capacity for safety analysis and risk emergency decision-making in hydraulic and hydroelectric engineering.